China’s position in its relations with the SCO observer-states - Zhabina, Zh. R.; Stambulov, S. B. (International relations and international law Journal, 2016)
The article defined the relevance of expanding the Shanghai Cooperation Organization (SCO) at the present stage. The discusses China’s strategy with respect to SCO observer-countries, as well as Afghanistan and Turkmenistan. The authors consider the interests of the SCO observer-countries in the organization, as well as the position of China and Russia. Attention is paid to the question of criteria for membership in the SCO, on the basis of the founding documents. Analyzes the problems and prospects of the SCO expansion at the present stage. The article defines the position and interests of China on the issue of participation in the SCO Mongolia, India and Pakistan. And also, the authors examine the issues associated with entry into the SCO Iran and Afghanistan, China looks to join the SCO Turkmenistan. The authors conclude that the increase in the membership of the SCO in the near future will not happen.